2020
DOI: 10.1002/dad2.12026
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of ATN Alzheimer biomarkers: 60‐month follow‐up results from the Argentine Alzheimer's Disease Neuroimaging Initiative

Abstract: Purpose To describe results of the Amyloid, Tau, Neurodegeneration (ATN) research framework classification in the Argentine‐Alzheimer's Disease Neuroimaging Initiative (arg‐ADNI) cohort. Methods Twenty‐three patients with mild cognitive impairment (MCI), 12 dementia of Alzheimer's type (DAT), and 14 normal controls were studied following the ADNI2 protocol. Patients were categorized according to presence or absence of the biomarkers for amyloid beta (Aβ; A: amyloid positron emission tomography [PET] scan or ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…82 Inspections revealed that only two patients had the A-T-N+ profile, one of whom received the diagnosis of hippocampal sclerosis probably due to TDP43 proteinopathy and the other was inconclusive. However, other authors 83 recently reported that some individuals with amnestic MCI progressed to clinical AD dementia within all four major A/T/N groups including A-T+N+ and A-T-N-. They suggested that when selecting individuals for research, a combination of the A/T/N framework and clinical status may be necessary because the prognostic value of the former depends on the latter.…”
Section: Cost Of Biomarkers (Prioritymentioning
confidence: 91%
See 1 more Smart Citation
“…82 Inspections revealed that only two patients had the A-T-N+ profile, one of whom received the diagnosis of hippocampal sclerosis probably due to TDP43 proteinopathy and the other was inconclusive. However, other authors 83 recently reported that some individuals with amnestic MCI progressed to clinical AD dementia within all four major A/T/N groups including A-T+N+ and A-T-N-. They suggested that when selecting individuals for research, a combination of the A/T/N framework and clinical status may be necessary because the prognostic value of the former depends on the latter.…”
Section: Cost Of Biomarkers (Prioritymentioning
confidence: 91%
“…Because only a limited number of patients will have access to such services, the feasibility of costly and still non‐specific dementia biomarkers in LACs needs to be further assessed. For instance, conversion rates to Alzheimer's disease (AD) after 5‐year follow‐up is about 50% for biomarkers positive (Amyloid + Tau + Neurodegeneration: A‐T‐N+ patients) 82 . Inspections revealed that only two patients had the A‐T‐N+ profile, one of whom received the diagnosis of hippocampal sclerosis probably due to TDP43 proteinopathy and the other was inconclusive.…”
Section: Knowledge Creationmentioning
confidence: 99%
“…24 The new A/T/N classification by Jack et al, 13,25 was applied to this population. 26 The results are shown in Figure 2.…”
Section: Fleni Experience: Multimodal Approach and International Networkmentioning
confidence: 99%
“…After a 5-year follow-up, the conversion rate from MCI to dementia was 85% in A+T+N+ patients and 50% in A-T-N+ patients. 26 When describing the clinical phenotype of a neurodegenerative patient, we currently report the brain region affected by the disease, with light reference to etiology. This form of classification seems now to be an outdated neurological concept that will likely be replaced in the near future by detailed information on cognitive proteinopathy findings.…”
Section: Fleni Experience: Multimodal Approach and International Networkmentioning
confidence: 99%
See 1 more Smart Citation